Redes biopoliméricas semi-interpenetradas entre β-glucana e poli(líquidos iônicos) como suporte de imobilização de microalgas - Godoi, Fábio Figueira de (Universidade Federal de São Carlos, 2026)
Polysaccharides have attracted considerable attention as environmentally friendly polymers due to their inherent biodegradability and biocompatibility, making them highly suitable for biomaterial applications. Their use as biodegradable materials has steadily increased over recent decades because of their wide range of applications in the pharmaceutical, biomedical, food, and cosmetic industries. Within the framework of the circular bioeconomy, biorenewable resources represent a promising strategy to meet the growing demand for technologically advanced materials derived from biomass. In this context, ionic liquids (ILs), often regarded as "green solvents," provide solutions to several challenges associated with biomass processing. More recently, however, their applications have expanded to the development of technologically relevant materials for energy storage, water treatment, and the transport and storage of gases such as CO₂. The aim of this project is to develop ionic gels as support materials for microalgae growth, providing an innovative platform for microalgae cultivation. The proposed gels consist of semi-interpenetrating polymer networks (semi-IPNs) formed by the biopolymer β-glucan—extracted from an abundant yet unconventional biomass source, lichens—and polymerizable ionic liquids. The optimization of polymerization reactions is one of the main focuses of this work, together with the chemical characterization of the resulting materials using spectroscopic techniques.
Semi-interpenetrating biopolymer networks composed of β-glucan and poly(ionic liquids) for microalgae immobilization
Keywords: Géis iônicos; β-glucana; Líquidos iônicos; Cultivo de microalgas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 9. Indústria, Inovação e Infraestrutura; 14. Vida na Água